IMPLEMENTASI KEBIJAKAN DANA DESA DALAM MENUNJANG PEMBANGUNAN DAN PEMBERDAYAAN DIDESA SUMBER MAKMUR TAHUN 2016 – 2018 - Robi Wardoni (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2020)
The vast area of ??Sumber Makmur Village means that equitable development and empowerment have not been maximally implemented according to the wishes of the community, the limited budget for the Village Fund is a factor that affects the success or failure of implementing the policies that have been planned. The research aims to describe the implementation of the Village Fund Policy in Supporting Development and Empowerment in 2016 - 2018. The study was conducted in Sumber Makmur village, Mukomuko Regency. The research method used is qualitative with two types of data sources, namely: primary data sources obtained from key informants consisting of 7 people, this number is considered sufficient to represent the Sumber Makmur community, secondary data obtained by the second source, namely: literature study of supporting or related literature with research. The research instrument was an interview guide to several informants with a prepared question format using an android mobile recorder application. Data analysis was performed by data reduction, data display, and conclusion drawing. The research refers to six aspects of the van Meter and van Horn (1975) model. It is known that the implementation of Village Fund policies in supporting development in Sumber Makmur village, Mukomuko Regency in 2016 - 2018 can be categorized as good, from the aspects of policy standards and targets, characteristics of implementing agents, social, economic and political conditions and Implementor Disposition. From the aspect of resources, communication between organizations and strengthening activities is categorized as quite good. It is known that the implementation of Village Fund policies in supporting empowerment in Sumber Makmur village, Mukomuko Regency in 2016-2018 can be categorized as good, from the aspects of policy standards and targets, communication between organizations and strengthening activities, social, economic and political conditions. From the aspect of resources, the characteristics of the implementing agency, Implementor Disposition are categorized as quite good.